Effect of Age-Dependent Parasitism in Eggs of Tuta absoluta (Lepidoptera: Gelechiidae) on Intraguild Predation Between Nabis pseudoferus (Hemiptera: Nabidae) and Trichogramma brassicae (Hymenoptera: Trichogrammatidae). Issue 3 (24th June 2019) - Mohammadpour, Marzieh; Hosseini, Mojtaba; Karimi, Javad; Hosseininaveh, Vahid
Abstract: The tomato leafminer, Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae), is a destructive pest of tomato that can cause up to 100% yield loss. The predatory bug Nabis pseudoferus (Remane) (Hemiptera: Nabidae) and the parasitoid Trichogramma brassicae (Bezdenko) (Hymenoptera: Trichogrammatidae) are natural enemies of this pest. Since the interaction between predators and parasitoids in different trophic levels including intraguild predation (IGP) can decrease or increase the efficiency of natural enemies, the effects of age-dependent parasitism of host eggs on IGP between these two species were investigated under laboratory conditions. In no-choice and choice preference tests, the predatory bug was exposed to 40 parasitized and nonparasitized eggs of different ages (24, 48, and 72 h old). Investigation of switching behavior was conducted using various combinations of tomato leafminer eggs (30:90, 45:75, 60:60, 75:45, and 90:30 nonparasitized:parasitized eggs) using eggs of different ages (24, 48, and 72 h old). In no-choice tests, the highest feeding rate of the predatory bug was 39.21 ± 0.36 eggs on 24-h-old nonparasitized eggs and the lowest feeding rate was 1.4 ± 0.80 eggs on 72-h-old parasitized eggs. In choice tests, comparison of the Manly's β indices indicated that the predatory bug preferred to feed on nonparasitized eggs with 48- and 72-h-old eggs, but there was no significant preference for the 24-h-old eggs. Results of switching test showed that the linear regression between Manly's β index and different ratios of nonparasitized eggs to parasitized and nonparasitized eggs was not significant in 72-h-old eggs. However, this regression was significant with 24- and 48-h-old eggs and the predator's preference was dependent upon the ratio of nonparasitized and parasitized tomato leafminer eggs. Results of the current study showed that the increasing age of parasitized egg decreased intensity of IGP between N. pseudoferus and T. brassicae.